A research on the stability of repair-welding for a great truss under the load - Myong Il Kim; Ju Chol Kwak (Talenta Publisher, 2022)
In this paper, we developed the direct repair welding method without eliminating the load when the repair welding of the great steel truss is going. According to the information about the process and data systematized, working for eliminate defect of welding joint and analyzing used FEM on the stability of the process and result of welding-repair were scientific more than the last time at the great structure. When do this we did not eliminate defect from the part of joint and so it’s not necessity to use any Jackie and turning back. The result of analysis and construction show that this method is very useful in the practice and by then the problem of stability solved clearly and perfectly and the time and efforts had consumed.